2020
DOI: 10.1183/16000617.0181-2019
|View full text |Cite|
|
Sign up to set email alerts
|

Desquamative interstitial pneumonia: a systematic review of its features and outcomes

Abstract: BackgroundDesquamative Interstitial Pneumonia (DIP) is a rare form of idiopathic interstitial pneumonia (IIP). Data on clinical features, aetiology, prognosis and effect of treatment strategies are limited. We aimed to collect all published cases to better characterise DIP.MethodsA systematic literature search was performed for all original cases of adult patients with histopathologically-confirmed DIP. Individual patient data were extracted and summarised.ResultsWe included 68 individual cases and 13 case ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
38
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 80 publications
(64 reference statements)
0
38
0
3
Order By: Relevance
“…La neumonía intersticial descamativa (NID) es un padecimiento raro: solamente se han reportado 362 casos en adultos, la mayoría entre fumadores [ 1 ]. En niños, no había consenso sobre su etiología y mecanismo patológico en los 41 artículos escritos en inglés hallados en la literatura hasta 2020 [ 1 , 2 , 3 ]. Hasta donde sabemos, solamente tres de los casos de NID reportados en niños presentaron insuficiencia renal asociada [ 4 ], y ninguno mostró un deterioro rápido y fatal en pacientes menores de 2 años.…”
Section: Introductionunclassified
“…La neumonía intersticial descamativa (NID) es un padecimiento raro: solamente se han reportado 362 casos en adultos, la mayoría entre fumadores [ 1 ]. En niños, no había consenso sobre su etiología y mecanismo patológico en los 41 artículos escritos en inglés hallados en la literatura hasta 2020 [ 1 , 2 , 3 ]. Hasta donde sabemos, solamente tres de los casos de NID reportados en niños presentaron insuficiencia renal asociada [ 4 ], y ninguno mostró un deterioro rápido y fatal en pacientes menores de 2 años.…”
Section: Introductionunclassified
“…Desquamative interstitial pneumonia (DIP) is a rare disorder: only 362 cases have been reported in adults, mostly among smokers (1). In children, its etiology and pathomechanism were far from reaching consensus in the 41 English-language articles found in the literature until 2020 (1)(2)(3). To the best of our knowledge, only three of the reported DIP cases in children presented with associated kidney failure (4), and not one featured rapid and fatal deterioration in patients below 2 years old.…”
Section: Introductionmentioning
confidence: 99%
“…Publications of series are scarce and spread over many years, limiting access to synthetic information. In the current issue of the European Respiratory Review, HELLEMONS et al [16] performed a systematic literature search of DIP, and reviewed a total of 362 cases of DIP from 13 case series and 68 individual cases in adults published between 1965 and 2019. They reported dyspnoea and cough as the most common presenting symptoms, and presence of a restrictive physiology in 71% of cases with reduced diffusion capacity.…”
mentioning
confidence: 99%
“…While these results were not surprising, the systematic review provides us with a much more accurate overview than previously available from individual cases or small series. Furthermore, HELLEMONS et al [16] identified data regarding treatment received in a majority of cases. Removal of the suspected culprit and initiation of glucocorticoids were the most frequent treatments.…”
mentioning
confidence: 99%
See 1 more Smart Citation